Implementation of the Integrated Stunting Reduction Acceleration Program at the Wonogiri District Health Office - Salma Nur Farida; Iik Sartika; Syefira Ayudia Johar (Formosa Publisher, 2023)
Stunting remains a global concern, affecting children's cognitive development and health. One of the districts that experienced an increase in the prevalence of stunting based on the SSGI results is Wonogiri Regency where in 2021 it was 14% while in 2022 it became 18%. This study aims to analyze the implementation of an integrated stunting reduction acceleration program at the Wonogiri Regency Health Office. This research is a qualitative descriptive study. Data collection using in-depth interviews, observation, and documentation. Validation in this study used source triangulation and method triangulation.The research findings, based on the Van Meter and Van Horn implementation model analysis, indicate that aspects of policy size and objectives, inter-organizational communication and implementing activities, agency characteristics, and implementing dispositions have been successful. However, there are still some aspects that have not been achieved well, such as the lack of financial resources provided and the economic and social conditions of the community that do not fully support the success of the integrated stunting reduction acceleration program. Based on this research, it is hoped that the Health Office will further strengthen the budget, especially for program targets and the community can be more cooperative in participating in activities, especially programs related to stunting prevention.